VISUAL-BASED LEARNING MEDIA IN THE FORM OF “ULAR TANGGA” GAME TO IMPROVE THE QUALITY OF LEARNING AND TEACHING - Robiuz Zaidah; Rima Firnanda; Nanin Verina Widya Putri; Robiuz Zaidah; Rima Firnanda; Nanin Verina Widya Putri (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
One of the Government policies mentioned in the points of the National Education Policy Direction in the field of Elementary and Secondary Education in 2001/2004 was to reform and strengthen the system. The quality of education at elementary level is demanded to always be better along with the world's changing. The teacher as the leading role in teaching and studying activity is expected to be able to use acceptable media to improve student's learning interest. Visual based teaching media in game formation is one of effective alternative media to improve studying quality. Children in elementary level have a tendency to play. Fun and relaxing situations will help children to increase their learning interest. There is a new paradigm recently that through playing children will be able to learn more and their studying activity will be more effective when the situation is set to be fun. The development of this learning media in the form of “ular tangga”game is aimed at giving discourse about alternative teaching media for elementary level. The use of this alternative media is expected to improve the quality of teaching and studying activities at elementary level.